Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1745-7254.2007.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Depside salts from Salvia miltiorrhiza improve myocardial microperfusion in rats using laser Doppler flowmetry

Abstract: Aim: To investigate the effects of depside salts from Salvia miltiorrhiza on myocardial microperfusion and systemic hemodynamics in open-chest anaesthetized Sprague-Dawley rats. Methods: Myocardial microperfusion was measured by laser Doppler flowmetry with a needle probe; cardiac output (CO) was determined using ultrasonic Doppler flowmetry. Other hemodynamic parameters, including femoral artery blood pressure, cardiac inotropy, and systemic vascular resistance (SVR) were simultaneously recorded by the PowerL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Our previous studies indicated that MLB attenuated myocardial ischemia-reperfusion injury in Sprague-Dawley (SD) rats [15]. It remains unclear whether MLB can improve microcirculation dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that MLB attenuated myocardial ischemia-reperfusion injury in Sprague-Dawley (SD) rats [15]. It remains unclear whether MLB can improve microcirculation dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the antioxidative property of MLB is particularly impressive because its antioxidative effect is reported to be greater than that of α-lipoic acid [9], a super antioxidant available as a dietary supplement or pharmaceutical drug in many countries. MLB was able to reduce the size of myocardial infarction, suppress ischemia/reperfusion (I/R)-induced cardiomyocyte apoptosis, and improve myocardial microperfusion [10], which were related to, at least in part, its antioxidative activity [11]. In addition to the beneficial effects on the ischemic heart, MLB was also able to exert neuroprotective effects against ischemic strokes [12].…”
mentioning
confidence: 99%
“…It can also reduce the incidence of contrast-induced nephropathy after PCI and is more effective than normal saline [15] . In addition, it has been confirmed that intravenous administration of salvianolate can improve cardiac microcirculatory perfusion and increase cardiac output in rats [16] . Similarly, continuous intravenous salvianolate 10 mg/kg/day for 7 days can significantly improve myocardial microcirculatory reflow in an ischemia-reperfusion minipig model, as well as reduce oxidative stress and myocardial apoptosis [17] .…”
Section: Discussionmentioning
confidence: 94%
“…[ 15 ] In addition, it has been confirmed that intravenous administration of salvianolate can improve cardiac microcirculatory perfusion and increase cardiac output in rats. [ 16 ] Similarly, continuous intravenous salvianolate 10 mg/kg/day for 7 days can significantly improve myocardial microcirculatory reflow in an ischemia-reperfusion minipig model, as well as reduce oxidative stress and myocardial apoptosis. [ 17 ] However, there is no evidence to show the effectiveness of Salvianolate injection in the treatment of ISR.…”
Section: Discussionmentioning
confidence: 99%